2015
DOI: 10.1371/journal.pone.0116663
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of the Partec CyFlow MiniPOC for Absolute and Relative CD4 T-Cell Enumeration

Abstract: BackgroundA new CD4 point-of-care instrument, the CyFlow miniPOC, which provides absolute and percentage CD4 T-cells, used for screening and monitoring of HIV-infected patients in resource-limited settings, was introduced recently. We assessed the performance of this novel instrument in a reference laboratory and in a field setting in Senegal.MethodologyA total of 321 blood samples were obtained from 297 adults and 24 children, all HIV-patients attending university hospitals in Dakar, or health centers in Zigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Simpler disposable lateral flow strip systems like Visitect (Omega Diagnostics) and Zyomyx MyT4 (Mylan, USA) offer instrument free options [ 18 21 ]. Several published papers describe validation of these systems with varying approaches, reference platforms and outcomes [ 22 26 ]. The PIMA point-of-care instrument has been commercially available the longest and several validation, implementation and costing studies have been reported, including a recent meta-analysis of POC technology [ 11 , 26 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simpler disposable lateral flow strip systems like Visitect (Omega Diagnostics) and Zyomyx MyT4 (Mylan, USA) offer instrument free options [ 18 21 ]. Several published papers describe validation of these systems with varying approaches, reference platforms and outcomes [ 22 26 ]. The PIMA point-of-care instrument has been commercially available the longest and several validation, implementation and costing studies have been reported, including a recent meta-analysis of POC technology [ 11 , 26 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CyFlow miniPOC is based on flow cytometry and has been recently evaluated. Compared with the FACSCalibur (BD Biosciences) and FACSCount (BD Biosciences) as reference standards it showed low relative bias and good sensitivity at WHO defined thresholds[ 9 ]. The assay is performed on venous blood, has a rapid specimen processing time allowing for up to 250 patient tests/day and also enumerates CD4% values.…”
Section: Introductionmentioning
confidence: 99%
“…To put the performance of our device into context, the commercially available Alere PIMA™ has shown 94% and 96% sensitivities at 200 and 500 cells/μL thresholds, respectively 29, 30 . Similarly, the sensitivity of CyFlow® miniPOC was >95% at 200, 350 and 500 cells/μL thresholds 31 . It is important to keep in mind that the performance of these systems were observed in the field, and further field-validation is required with our presented system before direct comparisons can be made.…”
Section: Discussionmentioning
confidence: 90%